Mismatch Negativity Elicited by Verbal and Nonverbal Stimuli: Comparison with Potential N1 - Brückmann, Mirtes; Garcia, Michele Vargas (International Archives of Otorhinolaryngology, 2020)
Introduction Mismatch negativity (MMN) is a long latency auditory evoked potential, represented by a negative wave, generated after the potential N1 and visualized in a resulting wave.Objective To identify the time of occurrence of MMN after N1, elicited with verbal and nonverbal stimuli.Methods Ninety individuals aged between 18 and 56 years old participated in the study, 39 of whom were male and 51 female, with normal auditory thresholds, at least 8 years of schooling, and who did not present auditory processing complaints. All of them underwent audiologic anamnesis, visual inspection of external auditory meatus, pure tone audiometry, speech audiometry, acoustic immittance measures and the dichotic sentence identification test as a screening for alterations in auditory processing, a requirement to participate in the sample. The MMN was applied with two different stimuli, with these being da/ta (verbal) and 750 Hz and 1,000 Hz (nonverbal).Results There was a statistically significant difference between the latency values of the N1 potential and the MMN with the two stimuli, as well as between the MMN with verbal and nonverbal stimuli, and the latency of the MMN elicited with da/ta being greater than that elicited with 750 Hz and 1,000 Hz, which facilitated its visualization.Conclusion The time of occurrence of MMN after the N1 elicited with verbal stimuli was 100.4 ms and with nonverbal stimuli 85.5 ms. Thus, the marking of the MMN with verbal stimuli proved to be more distant from N1 compared with the nonverbal stimuli.
Keywords: evoked potentials; auditory; adult; hearing; auditory cortex